Optimizing chemical structure of surfactant for graphene exfoliation method for nanoelectronic devices applications - Azmi Mohamed (Tanjong Malim, 2019)
Optimizing chemical structure of surfactant for graphene exfoliation method for nanoelectronic devices applications by Azmi Mohamed